تعليمية النحو العربي في الطور الثانوي وفق المقاربة بالكفاءات: توصيف وتقويم - كحلة, هجيرة; الاشراف, جمال (جامعة الوادي - University of Eloued, 2022)
عالج هذا المقال قضية مدى تحقق أهداف المقاربة بالكفاءات من خلال تعليمية النحو العربي. وبعد استعراض المعطيات النظرية والعملية عبر استبيانات موجهة إلى أطراف العملية التعليمية في الطور الثانوي (الأستاذ، المتعلم) توصلت الدراسة إلى تحقيق نتيجة هامة مفادها: عدم تحقق أهداف هذه المقاربة نظرا للتطبيق الجزئي لها الذي مأتاه عدم التمكن من فهم هذه المقاربة بسبب النقص الكمي والنوعي للتكوين العلمي والبيداغوجي فيها والذي مردّه سوء النقل الديداكتيكي على مستوى [واضع المنهاج، الوسيط، منفذ المقاربة (الأستاذ)]. This article addresses the case for whether the competency-based approach in the learning of Arabic grammar reached its purported objectives or not. After examining all the theoretical and practical data in the form of surveys targeting all the sides of the learning process at the high school level (teacher, student) this study reached an important conclusion that states: The competency-based approach failed to reach its purported objectives due to the partial implantation of it. Caused by a lack of understanding of the approach that is stemming from a quantitative and qualitative deficit in the scientific and pedagogical training on the approach. due to the poor didactic transposition on the level of {the creator of the curriculum, the intermediary, the approach executer (the teacher).
the learning of arabic grammar at the secondary level using the competency-based approach:description and evaluation
مقال
Keywords: المقاربة بالكفاءات ، تعليمية النحو العربي ، الاستبيان ، التكوين العلمي والبيداغوجي ، النقل الديداكتيكي; the competency-based approach , the learning of Arabic grammar , survey , the scientific and pedagogical training , didactic transposition